ANALISIS DAYA SAING EKSPOR MINYAK NILAM INDONESIA: PENDEKATAN RCA, RSCA, DAN EPD PADA TIGA PRODUSEN UTAMA GLOBAL 2015-2024 - Renita Adella; Denny Saputera (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study analyzes the export competitiveness of Indonesia patchouli oil relative to its main global competitors (China, France, and the United States) for the 2015-2024 period. Despite Indonesia has a significant contribution to global trade, the industry faces challenges such as price fluctuations and increasing demand for sustainability standards. Utilizing Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), and Export Product Dynamics (EPD), this research provides a comprehensive evaluation of Indonesia’s competitive position. the findings indicate that Indonesia maintains a remarkably strong and stable comparative ad-vantage, with RCA value rising significantly from 4,982 in 2021 to 7,622 in 2024. Based on the EPD matrix, Indonesia’s export performance is position in the “Rising Star” quadrant, show a declining trend in competitiveness. The study concludes that strengthening Indonesia’s position requires a transformation toward a green economy and supply chain digitalization to ensure long-term resil-ience increasingly competitive international market.